Generational Novel in the Service of Settling Scores with History. Emigration, Escape and Expulsion in German Literature after 2000 - Jabłkowska, Joanna (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
Generational novel has been popular in German literature for about twenty years. This popularity can be explained by the need sum up the communicative memory comprising the traumatic events of the twentieth century that is coming to a close. This paper shows the specificity of the most recent generational novels, taking as examples Reinhard Jirgl’s Die Unvollendeten, Ulrike Draesner’s Sieben Sprünge vom Rand der Welt and Ursula Krechel’s Landgericht. The works are representative of the group but exceptional too, since they raise problems which until recently were taboo in the public discourse. Their leitmotif is forced emigration. Their characters are the descendants of both victims of war and (German) victims of expulsion, i.e., two antagonistic memory groups. One of the aims of the paper is to show the divergences in the experiences of the two groups, even though those divergences become gradually obliterated in the texts written from the twenty first century perspective.